2017
DOI: 10.1097/md.0000000000009367
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical parameters, microbiological effects and calprotectin counts in gingival crevicular fluid between Er

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Clinical outcome parameters of the 8 articles (7 studies) evaluating laser as monotherapy are shown in Table 3. In order to perform meta-analyses on the primary (i.e., PPD change) and secondary outcome measure (i.e., CAL change), 5 articles including the 6-month PPD and CAL changes and reporting on non-surgical mechanical instrumentation or laser monotherapy in one session were selected [54,56,[59][60][61].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Clinical outcome parameters of the 8 articles (7 studies) evaluating laser as monotherapy are shown in Table 3. In order to perform meta-analyses on the primary (i.e., PPD change) and secondary outcome measure (i.e., CAL change), 5 articles including the 6-month PPD and CAL changes and reporting on non-surgical mechanical instrumentation or laser monotherapy in one session were selected [54,56,[59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of the 8 articles (7 studies) evaluating laser monotherapy are summarized in Table 2 [54][55][56][57][58][59][60][61].…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 Manual and ultrasonic instruments are the most common used instruments for SRP. [7][8][9] The use of oscillating scalers and hand instruments improves not only clinical variables but also provokes microbial shifts to less periodontopathogens in the subgingival biofilm. 10 The combined use of hand and ultrasonic instruments is recommended and reduces disadvantages of each of both used types of instruments.…”
Section: Introductionmentioning
confidence: 99%